The oral administration of zinc sulfate in increasing the mass of pancreatic β cell and reducing the level of fasting blood glucose and glycated albumin in male wistar rats (Rattus norvegicus) with diabetes mellitus - Silvia Irani; Anak Agung Gede Budhiarta; I Gusti Made Aman (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: Diabetes mellitus (DM) is a degenerative disease that can accelerate the aging process. Zinc is a mineral that has antioxidant potential that can increase the cell growth and it also protects pancreatic β cell mass from cell death during diabetes. This study aimed to prove that oral administration of zinc sulfate could increase the pancreatic β cells mass and decrease the level of fasting blood glucose (FBG) and glycated albumin (GA) in male Wistar rats with DM. Methods: This research employed a pure experimental research with post test only control group design by using 36 male Wistar rats. The placebo group that administered with 1 cc of aquadest and the group of zinc that administered by oral zinc sulfate of 100 mg/kgBW in which had been dissolved with 1 cc of aquadest. The assessment of pancreatic β cell mass and FBG levels and glycated albumin were carried out after 30 days of treatment. Results: The analysis by using the Shapiro-Wilk test was distributed normally. The result of Laven’s test indicated that the distribution of data and variants of the groups were homogeneous. The comparative results of the two groups using an independent t-test, there were significant differences between both groups on the mass of pancreatic β cell and the level of fasting blood glucose and glycated albumin (p <0.05). Conclusion: The oral administration of zinc sulfate can increase the pancreatic β cell mass and decrease the level of FBG and glycated albumin in male Wistar rats with DM.